CD38 Causes Autophagic Flux Inhibition and Cardiac Dysfunction Through a Transcriptional Inhibition Pathway Under Hypoxia/Ischemia Conditions - Zhang, Xingyue; Li, Lingfei; Zhang, Qiong; Wei, Qinglin; Lin, Jiezhi; Jia, Jiezhi; Zhang, Junhui; Yan, Tiantian; Lv, Yanling; Jiang, Xupin; Zhang, Peng; Song, Huapei; et al. (Frontiers in Cell and Developmental Biology, 2020)
Induced autophagy is protective against myocardial hypoxia/ischemia (H/I) injury, but evidence regarding the extent of autophagic clearance under H/I and the molecular mechanisms that influence autophagic flux has scarcely been presented. Here, we report that CD38 knockout improved cardiac function and autophagic flux in CD38-/- mice and CD38-/- neonatal cardiomyocytes (CMs) under H/I conditions. Mechanistic studies demonstrated that overexpression of CD38 specifically downregulated the expression of Rab7 and its adaptor protein Pleckstrin homology domain- containing protein family member 1 (PLEKHM1) through nicotinamide adenine dinucleotide (NAD)-dependent and non-NAD-dependent pathways, respectively. Loss of Rab7/PLEKHM1 impaired the fusion of autophagosomes and lysosomes, resulting in autophagosome accumulation in the myocardium and consequent cardiac dysfunction under H/I conditions. Thus, CD38 mediated autophagic flux blockade and cardiac dysfunction in a Rab7/PLEKHM1-dependent manner. These findings suggest a potential therapeutic strategy involving targeted suppression of CD38 expression.